Tailoring morphologies of diamond thin films for neural stem cells culturing. Issue 12 (14th November 2013) - Babchenko, Oleg; Romanyuk, Nataliya; Jendelova, Pavla; Kromka, Alexander
<x xml:space="preserve">Abstract</x> A controllable growth of neural cells and/or neural stem cells (NSCs) on artificial substrates is highly attractive scientifically as motivated by neurological and neurodegenerative disease treatment. In this contribution, we report on human fetal NSCs attachment and growth on the diamond films. Diamond films of different morphologies were deposited by linear antenna microwave plasma system from H2/CO2/CH4 gas mixtures. We show that the employed NSC lines attach to the oxidized diamond surface rather than hydrogenated. The influences of nanocrystalline diamond morphology (flat film, porous structure, or nano‐rods) and surface treatment (oxidized/hydrogenated or laminin coated films) are systematically studied after 8‐day cells seeding.